Flexible Modes of Assessment in Digital Learning through Asynchronous Course Delivery - EGEDE, Bernadette Amukahara Joy (Ilorin Journal of Education, 2023)
The huge impact made by the advances in Information and Communication Technology (ICT) and rapid development in contemporary society on our educational systems calls for prompt and adaptive responses in addition to adequate preparedness from all stakeholders, especially educators for effective service delivery. A significant offshoot of this impact is the increased flexibility in teaching and learning at all levels of education, which has informed the adoption of blended /hybrid modes of education delivery in higher institutions in Nigeria. As the popularity of online teaching via the blended/ hybrid mode is growing, the complexity of assessing various levels and domains of achievement in flexible learning is becoming an emerging phenomenon that is attracting the attention of educators in tertiary institutions. Which assessment designs and procedures should be employed in the totally/blended online teaching to achieve the desired quality assurance of learning outcomes? This paper addresses the current explanation of flexible learning in terms of open and distributed/distance learning and presents an overview of asynchronous course delivery as practiced in tertiary institutions. In addition, it presents acceptable web-based assessment frameworks suitable for asynchronous learning modes, and quality online assessment models that yield valid assessment results.